In Vitro α-Glucosidase Enzyme Inhibition Activity Test of Water Extract From Sintok (Cinnamomum sintoc Blume) Bark - Saksono, Astrella Amanda Putri; Simanjuntak, Inana Ratu Soripada; Wahjudi, Mariana; Gondokesumo, Marisca Evalina (UI Scholars Hub, 2025)
Diabetes mellitus is a condition characterized by elevated blood glucose levels beyond the normal limits. One therapeutic approach for managing diabetes mellitus involves inhibiting the α-glucosidase enzyme, which plays a role in glucose absorption in the body. However, the use of oral antidiabetic drugs from the α-glucosidase inhibitor class often causes gastrointestinal side effects. Therefore, exploring natural materials as alternative treatments is a promising option. In Indonesia, one plant with potential as an alternative treatment is sintok (Cinnamomum sintoc Blume), a member of the Cinnamomum genus, which is widely utilized in traditional medicine for chronic diseases such as diabetes mellitus. This study aimed to evaluate the α-glucosidase inhibitory activity of a water extract of sintok bark. Preliminary tests were conducted to determine the optimal conditions for measuring α-glucosidase enzyme inhibition activity in vitro using a UV- vis spectrophotometer. The results showed optimal enzyme activity at a wavelength of 405 nm, an incubation time of 40 minutes, and a substrate concentration of 12.5 mM. The water extract of sintok bark exhibited the highest inhibitory activity at a concentration of 5 ppm, with an inhibition value of 28.66%, while acarbose, used as a positive control, achieved the highest inhibition value of 96.36% at a concentration of 4.5 ppm. In conclusion, the aqueous extract of sintok bark demonstrates inhibitory activity against the α-glucosidase enzyme, indicating its potential as a natural antidiabetic agent.